Secondary haemophagocytic lymphohistiocytosis in a child with brucellosis - Varahala, Ajay Mohan; Malava, Ranjeet; Veldandi, Sravanthi; Boppidi, Santosh Avinash; Kolachena, Varsha; G., Udaya Rani G. Rani; Nalamalapu, Divya; E. P., Rhaj Kumar; Moturi, Raviteja; Alladi, Aparna (International Journal of Contemporary Pediatrics, 2020)
Human brucellosis is a zoonotic infection, mostly caused by B. melitensis and usually presents as an acute febrile illness. Once considered rare in children, it is now recognized that brucellosis can affect persons of all ages, especially in areas where B. melitensis is the predominant species. Complications may affect any organ system. On the other hand Secondary Hemophagocytic lymphohistiocytosis (SHLH) can occur due to systemic infections, immunodeficiency, and underlying malignancies. (SHLH) is histologically characterized by excessive proliferation and activation of histiocytes or macrophages. Brucellosis associated with SHLH should be suspected whenever there is a prolonged fever along with hepatosplenomegaly and pancytopenia.